Accounts Payable, Intellectual Capital, and Corporate Value: Case Study of Food and Beverage Sector on IDX 2016-2020 - Wilujeng, Sri; Widodo, Heri (Indonesian Journal of Public Policy Review, 2024)
This quantitative study investigates the influence of account payable policy and intellectual capital on the value of companies within the food and beverages sub-sector listed on the Indonesia Stock Exchange. Purposive sampling was employed to select a sample of eight manufacturing companies for the period 2016-2020. Data were collected using documentation techniques and analyzed using SPSS. Results indicate that while the account payable policy significantly affects firm value, intellectual capital does not exhibit a significant impact. These findings shed light on the strategic importance of managing account payables for enhancing firm value in the food and beverages industry. Highlights : The study investigates the influence of account payable policy and intellectual capital on firm value in the food and beverages sector. Purposive sampling was used to select a sample of eight manufacturing companies listed on the Indonesia Stock Exchange. Findings reveal that while account payable policy significantly affects firm value, intellectual capital does not demonstrate a significant impact. Keywords: Account Payable Policy, Intellectual Capital, Firm Value, Food and Beverages, Indonesia Stock Exchange